2019
DOI: 10.3390/app9193973
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Spatial Coherence for Ultrasonic DMAS Beamforming in Multi-Angle Plane-Wave Imaging

Abstract: Ultrasonic multi-angle plane-wave (PW) coherent compounding relies on delay-and-sum (DAS) beamforming of two-dimensional (2D) echo matrix in both the dimensions PW transmit angle and receiving channel to construct each image pixel. Due to the characteristics of DAS beamforming, PW coherent compounding may suffer from high image clutter when the number of transmit angles is kept low for ultrafast image acquisition. Delay-multiply-and-sum (DMAS) beamforming exploits the spatial coherence of the receiving apertur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The FDMAS beamformer realizes superior resolution and contrast in comparison with the DAS beamformer because the multiply-and-sum operation corresponds to evaluation of signal coherence [ 2 ]. The FDMAS method is also used for coherent compounding in plane-wave imaging [ 4 6 ].…”
Section: Beamformingmentioning
confidence: 99%
“…The FDMAS beamformer realizes superior resolution and contrast in comparison with the DAS beamformer because the multiply-and-sum operation corresponds to evaluation of signal coherence [ 2 ]. The FDMAS method is also used for coherent compounding in plane-wave imaging [ 4 6 ].…”
Section: Beamformingmentioning
confidence: 99%
“…Any combination of DAS and DMAS beamforming can be applied to the 2D echo matrix in the RxCh direction and the TxEt direction to determine the final B-mode image pixel. The resultant four beamforming methods include 2D-DAS (i.e., CPWC) for 2D summation of the echo matrix, 2D-DMAS for DMAS beamforming in both of RxCh and TxEt directions [13], Rx-DMAS for coherent summation in the TxEt direction and then DMAS processing in the RxCh direction [12], and Tx-DMAS for coherent summation in the RxCh direction and then DMAS processing in the TxEt direction [11]. Given the time-compensated baseband signal s nk = a nk e jφ nk for the n-th RxCh in the k-th TxEt (i.e., the k-th PW transmit angle), the four beamforming methods can be formulated as:…”
Section: Dmas Beamforming In Multi-angle Pw Imagingmentioning
confidence: 99%
“…Several works have been developed to extend DMAS beamforming for PW imaging using either the signal coherence of the echo matrix in the TxEt direction [11] or in the RxCh direction [12]. Recently, a novel DMAS operation has also been proposed to extract the 2D spatial coherence of echo matrix for further improvement of image quality [13].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by these findings, we preliminarily developed an alternative version of MV-DMAS beamforming specifically for multi-angle PW imaging at the conference of IUS 2022 [ 35 ] and confirmed that the image resolution and contrast can be improved but at the cost of speckle quality in the background region. The degradation of speckle quality results from the intrinsic feature of the conventional DMAS algorithm in which a global p value is assigned to every image pixel regardless of its characteristics [ 36 ]. In this study, the performance of various MV beamforming methods in multi-angle PW imaging is firstly examined without considering the DMAS algorithm in order to find the optimal MV beamforming strategy in multi-angle PW imaging.…”
Section: Introductionmentioning
confidence: 99%